2014
DOI: 10.5505/apjes.2014.38247
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Uptake Efficiency in Plant Production and Negative Effects of Reactive Nitrogen on Environment

Abstract: ÖzetTarımsal üretimde toprağa uygulanan azotun bitkiler tarafından alınan miktarı üretim yönetim uygulamaları ve ürün çeşitlerine göre değişmekle birlikte ancak yarısı kadardır. Bitkiler tarafından kullanılamayan bu miktar ciddi ekonomik kayıp oluşturmakla birlikte önemli çevre ve sağlık problemlerine neden olmaktadır. Bu çalışma ile bitkisel üretimde azot alım etkinliğinin düşüklüğü ve reaktif azotun çevre üzerine olumsuz etkilerine dikkat çekilerek azot alım etkinliğini artırmaya ve reaktif azotun çevreye ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 18 publications
0
8
0
5
Order By: Relevance
“…Fertilizers mostly used by the 369 farmers participating in the study in agricultural production; It was determined that 75.61% farm manure, 60.43% DAP, 55.56% urea, 30.89% composite 20-20, 23.04% ammonium sulphate, 21.95% compound 15-15-15 (Yıldırım (2020) As in the world, the most fertilizer consumption is seen in nitrogenous fertilizers, followed by phosphorus and potash fertilizers respectively (Sağlam 1991). Indeed Karaşahin (2014) of approximately 65% of total fertilizer consumption in Turkey report that consists of nitrogen fertilizer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilizers mostly used by the 369 farmers participating in the study in agricultural production; It was determined that 75.61% farm manure, 60.43% DAP, 55.56% urea, 30.89% composite 20-20, 23.04% ammonium sulphate, 21.95% compound 15-15-15 (Yıldırım (2020) As in the world, the most fertilizer consumption is seen in nitrogenous fertilizers, followed by phosphorus and potash fertilizers respectively (Sağlam 1991). Indeed Karaşahin (2014) of approximately 65% of total fertilizer consumption in Turkey report that consists of nitrogen fertilizer.…”
Section: Resultsmentioning
confidence: 99%
“…As in the world, the most fertilizer consumption is seen in nitrogenous fertilizers, followed by phosphorus and potash fertilizers respectively. Indeed Karaşahin (2014) of approximately 65% of total fertilizer consumption in Turkey report that consists of nitrogen fertilizer. The amount of pesticide consumption increased 3.4% between the years 1983-1993 in Turkey between 1993 and 1995 rose to 18.5%.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing N doses were decreased the NU p E ( Table 2). NU p E is that beneficial N in soil is proportional to amount taken by plant (Karasahin, 2014). Kamara et al (2003) and Kara (2006) reported that the NU p E was decreased depending on increasing N doses.…”
Section: Resultsmentioning
confidence: 99%
“…AKE'nin artırılması üreticiler için üretim maliyetlerinin düşmesini beraberinde getirecektir. Karaşahin (2014), AKE'yi etkileyen faktörleri ve iyileştirilmesi için yapılması gerekenleri yaptığı literatür taraması ile kapsamlı bir şekilde ortaya koymuştur. Buna göre; AKE'yi iyileştirmek için ürün rotasyonu (münavebe), gübreleme öncesinde toprakta bulunan azot miktarının göz önüne alınması, baklagil bitkilerinin üretim sistemine dahil edilmesi, hibrit veya kültür çeşitlerinin kullanılması, uygun toprak işleme, azot kaynağı olarak amonyumun kullanılması, zamanında ve yapraktan azotun uygulanması ve gelişmiş sulama ve gübreleme yönetim uygulamalarının yapılması uygulanabilecek başlıca yaklaşımlardır (Raun et al, 2002;Das et al, 2005;Battilani et al, 2008;Büyük, 2016).…”
Section: Introductionunclassified
“…Azot kullanımının bu önemine istinaden tarımsal üretimde azot kullanım etkinliğinin (AKE) doğru olarak ölçülmesi kaynak etkin Tarım-Gıda zincirinin sağlanma imkânlarının ortaya konması bakımından oldukça önemlidir (ör. EC, 2011;2014).…”
Section: Introductionunclassified